The FDG Pattern of Autonomously Functioning Thyroid Nodules Correlates With Thyroid-Stimulating Hormone and Histopathology. (28th February 2023) - Piccardo, Arnoldo; Fiz, Francesco; Bottoni, Gianluca; Massollo, Michela; Puntoni, Matteo; Catrambone, Ugo; Foppiani, Luca; Bertagna, Francesco; Albano, Domenico; Trimboli, Pierpaolo
Abstract : Purpose of the report: Whereas the 18 F-FDG PET/CT pattern of malignant thyroid neoplasia is known, the glucose uptake of autonomously functioning thyroid nodules (AFTNs) has not been fully investigated. We aimed to analyze the FDG uptake of AFTNs and its correlation with clinical, laboratory, ultrasonography, and histological features. Methods: We retrospectively analyzed the records of all AFTN patients from 2 centers, in which an 18 F-FDG PET/CT, thyroid function tests, and neck ultrasound were available within a 3-month window from the thyroid scintigraphy. Forty-five patients (35 female patients; median age, 65 years) were retrospectively included. The presence of FDG uptake was compared with the laboratory data and, whenever available, the histology. Results: Over a 36-month follow-up, 20 patients underwent surgery; 4 cancers, 10 follicular adenomas, and 6 follicular hyperplasias were found. Twenty-two AFTNs (48.9%) were FDG-positive, whereas the remaining 23 (51.1%) were not. Thyroid-stimulating hormone (TSH) was significantly lower in FDG-positive AFTNs than in negative ones (0.055 [0.02–0.42] vs 0.65 [0.2–0.96] mIU/L, P = 0.0018). On multivariate analysis, only TSH was independently associated with FDG uptake ( P = 0.008). On receiver operating characteristic curve analysis, TSH <0.08 mIU/L indicated FDG-positive AFTNs, with 64% sensitivity, 87% specificity, 4.88 positive likelihood ratio, and 0.42 negative likelihood ratio. In histologically proven benign lesions, TSH was significantly lower in follicular adenomas than in follicular hyperplasias ( P < 0.001). Patients with cancer had TSH in the low-normal range. Conclusions: Autonomously functioning thyroid nodules show heterogeneous uptake FDG pattern, which depends on histopathology and thyroid function. Particularly, follicular adenomas tend to display increased glucose uptake and suppressed TSH.